2018
DOI: 10.1021/acsami.8b11399
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Photo-Supercapacitor with a New Architecture Converts and Stores Solar Energy as Charge

Abstract: Photo-supercapacitors (PSCs) combine functions of energy harvesting and storage in a single device, and in this study, a new architecture for a PSC is designed and implemented. Cadmium sulfide (CdS) quantum dots/hibiscus (hb) dye co-sensitized TiO2 is used as the solar cell. Poly­(3,4-ethylenedioxypyrrole) (PEDOP)@manganese dioxide (MnO2) is employed as the counter electrode (CE) for the solar cell and also as the electrodes for the symmetric supercapacitor. The two ends of a long flat current collector suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 43 publications
1
40
0
1
Order By: Relevance
“…Recently, Das et al. employed CdS QDs/hibiscus (hb) dye cosensitized TiO 2 as a photoanode . Electropolymerized PEDOP@MnO 2 was used as both the CE for the solar cell and electrodes for the symmetric pseudocapacitor, while a PIC ([BuMeIm][CF 3 SO 3 ]; BuMeIm=1‐butyl‐3‐methylimidazolium) was employed as the non‐redox electrolyte.…”
Section: Planar‐type Pssmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Das et al. employed CdS QDs/hibiscus (hb) dye cosensitized TiO 2 as a photoanode . Electropolymerized PEDOP@MnO 2 was used as both the CE for the solar cell and electrodes for the symmetric pseudocapacitor, while a PIC ([BuMeIm][CF 3 SO 3 ]; BuMeIm=1‐butyl‐3‐methylimidazolium) was employed as the non‐redox electrolyte.…”
Section: Planar‐type Pssmentioning
confidence: 99%
“…Recently,D as et al employed CdS QDs/hibiscus( hb) dye cosensitized TiO 2 as ap hotoanode. [40] Electropolymerized PE-DOP@MnO 2 was used as both the CE for the solar cell and BuMeIm = 1-butyl-3-methylimidazolium) was employed as the non-redox electrolyte. These two parallel modulesa re linked by FTO modified glass.…”
Section: Three-electrode Pss Based On Qdsscsmentioning
confidence: 99%
“…Solar energy is readily available and the most abundant renewable resources on the earth, however, given the intermittent nature of solar energy, designing efficient solar charge–discharge system is one of the main trends for green energy development in the future . Recently, some research have investigated solar charging system, which is composed by solar cell and energy storage device. One of the critical issues needs to be addressed for efficient solar charging system is the power matching principle.…”
Section: Introductionmentioning
confidence: 99%
“…High power solar cell should the device exhibited a high energy density of 42.5 Wh kg −1 at 21.1 kW kg −1 due to the unique hollow structure with defined mesoporosity that allow efficient electrolyte diffusion/penetration and enlarge the electrolyte/electrode interface. [28] In our previous work, Co 3 6 ] 2 ·10H 2 O were prepared and used for symmetric supercapacitors, the structure and compositional advantages made the device presented an energy density of 35.15 Wh kg −1 at 1125 W kg −1 . [38] Therefore, all evidences demonstrated that PB/PBAs derivatives had promising prospect for ECs and batteries application with high energy density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation